DIFFERENTIAL DIAGNOSIS OF PROGENIC FORMS OF BITE AND ITS IMPORTANCE IN PREDICTING THE RESULTS OF ORTHODONTIC TREATMENT - P.S. Flis; K.V. Storozhenko (Український стоматологічний альманах)
Increased requirements of patients to the results of orthodontic treatment are forcing orthodontists to have a deep knowledge of the anatomy of the face, to know the structure and constituent elements of facial harmony, guided in species proportions and variations of structure of the facial skull.